190 COMPARISON OF CENTRAL PROJECTIONS FROM T12 SPINAL NERVE IN MUTANT HAIRLESS MICE VERSUS SWISS WEBSTER MICE. (1st January 2005) - Gilleon, C.; Mosconi, T.; Gruber, T.; Biehn, J.
Abstract : Recent studies have revealed extensive plasticity in cutaneous sensory terminals in mutant hairless (Hr) mice after hair loss, evidenced by a reorganization of cutaneous innervation and subsequent hyperinnervation in the epidermis over the entire body. Many of the fibers newly innervating the epidermis appear to be C fibers. Our study aimed to determine whether the remodeling seen in the peripheral territory of the T12 spinal nerve of Hr mice would be reflected in the spinal cord dorsal horn targets. We also assessed cells in the T11-L1 dorsal root ganglia contributing to T12 spinal nerve, identified by retrograde tracing with FluoroGold (FG) from the T12 nerve, to determine whether there are detectible biochemical alterations related to peripheral alterations. Sections from spinal cord dorsal horns and T11-L1 dorsal root ganglia from 8 Hr and 8 control Swiss-Webster (SW) mice were labeled by immunofluorescence using antibodies against calcitonin gene-related peptide (CGRP), galanin (GAL), and substance P, predominant C-fiber neuropeptides, and by lectin histochemistry using fluorescent-conjugated Griffonia simplicifolia (GSA) which identifies a discrete, non-peptidergic C-fiber population. In the table below: *mean area measurements (μm2) of labeled spinal cord territories; **mean cell number per section of immuno-/lectin-positive DRG cells identified by retrograde FG transport; and ***corresponding P values (significant at P ≤ 0.05). Our data revealed no significant differences between Hr and SW in the biochemistry of the FG-labeled neurons in the dorsal root ganglia of T11-L1 or in the patterns of central dorsal horn projections, suggesting that morphological changes to afferents in the periphery are not reflected centrally in the spinal cord of Hr . These data stand in contrast to a companion study examining similar issues in the trigeminal brainstem projections of Hr compared to SW, in which there is significant expansion of CGRP- and GSA-positive central territories. Collectively, these results suggest that there are differences in central processing of inputs from the body compared to inputs from the face in Hr .